RETRACTED ARTICLE: Tamoxifen suppresses brain metastasis of estrogen receptor-deficient breast cancer by skewing microglia polarization and enhancing their immune functions - Shih-Ying Wu; Sambad Sharma; Kerui Wu; Abhishek Tyagi; Dan Zhao; Ravindra Pramod Deshpande; Kounosuke Watabe (Breast Cancer Research)
Abstract Background Brain metastasis of breast cancer exhibits exceedingly poor prognosis, and both triple negative (TN) and Her2+ subtypes have the highest incidence of brain metastasis. Although estrogen blockers are considered to be ineffective for their treatment, recent evidence indicates that estrogen blockade using tamoxifen showed certain efficacy. However, how estrogen affects brain metastasis of triple negative breast cancer (TNBC) remains elusive. Methods To examine the effect of estrogen on brain metastasis progression, nude mice were implanted with brain metastatic cells and treated with either estrogen supplement, tamoxifen, or ovariectomy for estrogen depletion. For clinical validation study, brain metastasis specimens from pre- and post-menopause breast cancer patients were examined for microglia polarization by immunohistochemistry. To examine the estrogen-induced M2 microglia polarization, microglia cells were treated with estrogen, and the M1/M2 microglia polarization was detected by qRT-PCR and FACS. The estrogen receptor-deficient brain metastatic cells, SkBrM and 231BrM, were treated with conditioned medium (CM) derived from microglia that were treated with estrogen in the presence or absence of tamoxifen. The effect of microglia-derived CM on tumor cells was examined by colony formation assay and sphere forming ability. Results We found that M2 microglia were abundantly infiltrated in brain metastasis of pre-menopausal breast cancer patients. A similar observation was made in vivo, when we treated mice systemically with estrogen. Blocking of estrogen signaling either by tamoxifen treatment or surgical resection of mice ovaries suppressed M2 microglial polarization and decreased the secretion of C-C motif chemokine ligand 5, resulting in suppression of brain metastasis. The estrogen modulation also suppressed stemness in TNBC cells in vitro. Importantly, estrogen enhanced the expression of signal regulatory protein α on microglia and restricted their phagocytic ability. Conclusions Our results indicate that estrogen promotes brain metastasis by skewing polarity of M2 microglia and inhibiting their phagocytic ability, while tamoxifen suppresses brain metastasis by blocking the M2 polarization of microglia and increasing their anti-tumor phagocytic ability. Our results also highlight a potential therapeutic utility of tamoxifen for treating brain metastasis of hormone receptor-deficient breast cancer.